Two new water mite species of the genus Lebertia (Acari: Hydrachnidia: Lebertiidae) from Turkey - Esen, Yunus; Dilkaraoglu, Sibel; Erman, Orhan; Gerecke, Reinhard (Taylor & Francis Ltd, 2013)
Two water mite species new to science are described of the genus Lebertia, collected from running waters and springs in Eastern Anatolia, Turkey. Lebertia (Brentalebertia) anatolica Esen and Dilkaraoglu, sp.nov. as the fourth known species of the subgenus Brentalebertia Gerecke, 2008 and Lebertia (s. str.) erzurumensis Esen and Erman, sp. nov. as a sister species of L. pusilla. Lebertia (s. str.) subtilis Koenike, 1902 is recorded for the first time after the original description from Switzerland. It was found in a high-altitude spring, rich in gravel substrata and moss vegetation. http://www.zoobank.org/urn:lsid:zoobank.org:pub:6D5992C0-CB77-4651-B93C-17AA5015F027
Keywords: water mites; running waters; springs; Lebertiidae; Turkey